AN ANALYSIS OF CODE-MIXING IN FEMALE DAILY NETWORK VIDEO BLOG - Pangkerego, Claudia Maria; Liando, Nihta V. F.; Mamentu, Agustine C. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The aim of this research is to investigate the use of the type and forms code-mixing. To accomplish this investigation, which is supported theory from expert, by using internet platform media and the object as shown on the Female Daily Media blog YouTube channel. Descriptive quantitative is the method used in this study and the data collection instrument uses observation techniques. The results of this study showed that these two phases dominantly using a single word founded in utterances. The researcher concluded in this study that in the three groups of code-mixing forms, the use of single words was most common in mixed forms where the combined usage of foreign language words was more dominant. It is our mission that this research will serve as a resource for future researchers who will be interested in developing new phenomena and accurate data in the application of English or other foreign languages.